Predictors of Successful Weight Loss in Extremely Obese Individuals Undergoing Roux-en-Y Gastric Bypass Surgery - Sophia Helena Camargos Moreira; Jacqueline Isaura Alvarez-Leite; Renan Pedra Souza; Giulia Carregal Resmini; Cristina Maria Mendes Resende; Luiz de Marco; Luciana Bastos-Rodrigues (Journal of Obesity & Metabolic Syndrome)
Background : Roux-en-Y gastric bypass (RYGB) is a standard treatment for severe obesity, but some patients do not achieve the expected success in weight loss. The aim of this study was to evaluate possible predictors of weight loss after RYGB. Methods : Sixty-three patients were included. Pre- and postoperative data were collected from medical records, including comorbidities, anthropometry, energy/macronutrient intake, and physical activity level (PAL). Variants in the brain-derived neurotrophic factor (BDNF; rs6265) and lysophospholipase like 1 (LYPLAL1; rs4846567) genes were investigated. Excess weight loss (EWL) >50% was considered to be successful weight loss (SWL). Logistic regression models were used to verify predictor variables. Results : Participants’ median preoperative body mass index (BMI) was 53 kg/m2 (interquartile range, 46 to 58). At 12 and 24 months after surgery, EWL was 63% and 67%, and the failure rate was 19% and 16%, respectively. The individuals with insufficient weight loss (IWL) after 12 months had higher preoperative weight, BMI, and overweight. At 24 months, lowest frequency of individuals with SWL in the first year was found in the IWL group. No significant differences were found between the groups in dietary intake and PAL. In the logistic regression, high initial BMI was a predictor of the worst response in both periods, and high initial total weight loss was a predictor of a better response at 24 months. The polymorphism analysis did not show differences between groups in either gene. Conclusion : Lower preoperative BMI and greater weight loss at 12 months were predictors of SWL after RYGB.